2020
DOI: 10.1083/jcb.201702123
|View full text |Cite
|
Sign up to set email alerts
|

Tex19.1 inhibits the N-end rule pathway and maintains acetylated SMC3 cohesin and sister chromatid cohesion in oocytes

Abstract: Age-dependent oocyte aneuploidy, a major cause of Down syndrome, is associated with declining sister chromatid cohesion in postnatal oocytes. Here we show that cohesion in postnatal mouse oocytes is regulated by Tex19.1. We show Tex19.1−/− oocytes have defects maintaining chiasmata, missegregate their chromosomes during meiosis, and transmit aneuploidies to the next generation. Furthermore, we show that mouse Tex19.1 inhibits N-end rule protein degradation mediated by its interacting partner UBR2, and that Ubr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 72 publications
(177 reference statements)
0
8
0
Order By: Relevance
“…In Drosophila , a proper nutrient state during oogenesis is critical for the establishment of the unique quiescent state of oocytes (Sieber et al, 2016 ). In mammals, primordial oocytes are retained in a quiescent state that is prolonged with aging, and proteostatic regulation during the primordial stage is critical for the long‐term maintenance of chromosomal cohesin (Burkhardt et al, 2016 ; Reichmann et al, 2020 ). Mouse oocytes have a functional insulin signaling cascade (Acevedo et al, 2007 ), which may be involved in the transcriptional response to CR.…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila , a proper nutrient state during oogenesis is critical for the establishment of the unique quiescent state of oocytes (Sieber et al, 2016 ). In mammals, primordial oocytes are retained in a quiescent state that is prolonged with aging, and proteostatic regulation during the primordial stage is critical for the long‐term maintenance of chromosomal cohesin (Burkhardt et al, 2016 ; Reichmann et al, 2020 ). Mouse oocytes have a functional insulin signaling cascade (Acevedo et al, 2007 ), which may be involved in the transcriptional response to CR.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that mobilization of LINE-1 ( Long interspersed nuclear element 1) retrotransposons is restricted by TEX19.1 in mouse embryonic stem cells [ 44 ] may explain the placental dysfunction and small size. Lastly, it was recently reported that TEX19.1 maintains acetylated SMC3 (Structural Maintenance of Chromosome 3) and sister chromatid cohesion in postnatal oocytes and prevents aneuploidy [ 45 ].…”
Section: Tex Gene Expression and Function In The Mousementioning
confidence: 99%
“…[ 26 ] TEX19.1 in mouse oocytes contributes to preventing homologue chromosome segregation errors and premature sister chromatid separation during meiosis I. [ 27 ] In the absence of TEX19.1, mouse oocytes missegregate their chromosomes during meiosis I and transmit aneuploidies to the next generation. [ 27 ] These post‐translational modifications are conserved in mammals, which may partially explain the high frequency of chromosome segregation errors in mammalian eggs.…”
Section: Introductionmentioning
confidence: 99%